Annual Report 2001-2002 - Planning Commission (Planning Commission, 2001)
Apart from financial provisioning for plan programmes and schemes of the Central Sector, the discussions for the Annual Plan 2001-02 highlighted the need to effectively utilise the available resources. It was pointed out that even what has been provided for by way of plan allocation is not reflected well in terms of physical achievements. Emphasis was placed on systematic improvements in monitoring mechanisms, design and structuring of plan schemes, with a view to improve their efficacy in obtaining the staled objectives.
Planning Commission Government of India
Planning Commission Government of India